Endoscopic sphincterotomy and risk of cholangiocarcinoma: a population-based cohort study in Finland and Sweden - Strömberg, Cecilia; Böckelman, Camilla; Song, Huan; Ye, Weimin; Pukkala, Eero; Haglund, Caj; Nilsson, Magnus (Endoscopy International Open, 2016)
Background and study aims: Elevated long-term risk of cholangiocarcinoma is reported after endoscopic sphincterotomy (ES), but in a previous study we found a trend towards a decreased risk. The aim of this study was to evaluate the association in a larger cohort with a longer follow-up.Patients and methods: Data concerning all patients having had an inpatient endoscopic retrograde cholangiopancreatography (ERCP) were collected from the hospital discharge registries of Finland and Sweden. Incident cases of malignancy were identified through linkage to the nationwide Cancer Registries. Patients with a diagnosis of malignancy, before or within 2 years of the ERCP, were excluded. The cohorts were followed until a diagnosis of malignancy, death or emigration, or end of follow-up (end of 2010). The relative risk of malignancy was calculated as standardized incidence ratio (SIR) compared with the general population, inherently adjusting for age, gender, and calendar year of follow-up.Results: A total of 69 925 patients undergoing ERCP from 1976 through 2008 were included in the pooled cohort. ES was performed in 40 193 subjects. The risk of malignancy was elevated in the total cohort (SIR = 2.3; 95 % confidence interval [CI] 2.1 – 2.5) irrespective of whether ES was performed or not. The SIRs diminished with duration of follow-up.Conclusions: We found an elevated risk of malignancy both in the bile ducts alone and in the bile ducts, liver or pancreas together, after ERCP. The risk was the same, regardless of whether ES had been performed or not, so ES was unlikely to be the cause, and a common carcinogenic exposure previous to the ERCP procedure, possibly ductal gallstone disease, was more likely.